Construction automation : data handling in BIM environment - Nurul Afifa Khairul Anwar (Nanyang Technological University, 2020)
As Building Information Modelling (BIM) takes precedence in the construction industry, we see that there is a gap between quantity take-off and BIM. Quantity take-off is vital during the early stages of the project due to the costs estimations. Quantity Surveyors (QS) are still verifying quantities through 2-D plans instead of utilizing BIM to quicken their process. While BIM has undoubtedly improved productivity, BIM-based quantity take-off is not widely used due to various limiting factors. These limiting factors include the lack of cross-domain knowledge, the lack of vital information in the BIM model and the data inconsistency due to the way the model is constructed. This paper focuses on bridging the gap and creating an automated workflow that can be utilized by QS without having the need to be very skillful with the BIM authoring tool. This workflow also highlights the limitations behind built-in quantity take-off functions of the authoring tools – which can be further improved on by using the Application Programming Interface (API). Ultimately, this paper aims to create a bridge for quantity surveyors in utilizing BIM. By having more stakeholders utilizing BIM, it encourages seamless workflow between the different stakeholders, which would in turn further increase the productivity and encourage collaboration between the stakeholders for the project.